Analisis Pengaruh Harga Jual Biaya Oprasional dan Volume Penjualan Terhadap Pendapatan di Toko Champion Bangunan Kalabahi Kabupaten Alor Tahun 2022-2024 - Sabu, Junuius Menase Sau; Oni, J. E. Ahal; Maro, Yustina (Peneliti.net, 2026)
This study aims to investigate the influence of selling price, operating costs, and sales volume on revenue at Toko Champion Bangunan Kalabahi, Alor Regency, during the 2022-2024 observation period. This research employs a quantitative approach, with data collection techniques including observation, interviews, and documentation studies. The study utilizes secondary data, where the population and sample consist of the financial statements of Toko Champion Bangunan Kalabahi for the years 2022-2024. The statistical method employed is multiple linear regression analysis, utilizing the significance values of the t-test and F-test as benchmarks for hypothesis testing. Data processing was conducted using IBM SPSS 16 for Windows. The results of the study indicate that: 1). Partially, the selling price variable has a significance value of 0.000 (0.0%), which is lower than the alpha value of 0.05 (5%); therefore, the study accepts H1, stating that the selling price variable partially influences the revenue of Toko Champion Bangunan Kalabahi from 2022 to 2024, 2). Partially, the operating costs variable has a significance value of 0.004 (0.4%), which is lower than the alpha value of 0.05; thus, the study accepts H2, stating that the operating costs variable partially influences revenue, 3). Partially, the sales volume variable has a significance value of 0.004 (0.4%), which is lower than the alpha value of 0.05; hence, the study accepts H3, stating that the sales volume variable partially influences revenue, 4). Simultaneously, the variables of selling price, operating costs, and sales volume yield a significance value of 0.000 (0.0%), which is lower than the alpha value of 0.05; consequently, the study accepts H4, confirming that selling price, operating costs, and sales volume simultaneously influence the revenue of Toko Champion Bangunan Kalabahi from 2022 to 2024.